Corrosion resistant adhesive sol-gel

By applying a sol-gel coating containing organic corrosion inhibitors and surfactants on a metal substrate and applying an organic primer, the problem of difficulty in taking into account both adhesion and corrosion resistance in the prior art is solved, and high efficiency is achieved metal substrate protection.

CN119497738APending Publication Date: 2025-02-21THE BOEING CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380051673.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2023-05-05
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to maintain sufficient corrosion resistance while improving the adhesion and corrosion resistance of metal substrates, especially in the absence of corrosion inhibitors and primers of chromate.

Method used

A sol-gel coating containing about 3% to about 15% by weight of an organic corrosion inhibitor, a surfactant and an epoxy-containing organosilane, metal alkoxide and acid reaction product is applied thereto, an organic primer is applied thereto. Improve the adhesion and corrosion resistance of metal substrates.

Benefits of technology

It achieves good adhesion and corrosion resistance on metal substrates, while avoiding the use of chromate and meeting regulatory requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119497738A_ABST
    Figure CN119497738A_ABST
Patent Text Reader

Abstract

The invention relates to a substrate and a method for producing the substrate. The substrate has a metal substrate and a sol-gel coating disposed on the metal substrate. The sol-gel coating includes from about 3 wt% to about 15 wt%, by volume, of an organic corrosion inhibitor into the sol-gel. The sol-gel includes a reaction product of a surfactant and an epoxy-containing organosilane, a metal alkoxide, and an acid.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related applications

[0002] This application claims the benefit of priority to U.S. application No. 63 / 339,289, filed May 6, 2022, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Aspects of the present disclosure generally relate to corrosion-resistant sol-gel films for aerospace applications. Background Art

[0004] Metals used in the construction of aircraft, spacecraft, and other machinery, such as steel, aluminum, aluminum alloys, and galvanized metals, are susceptible to corrosion. Chromates, such as the zinc salt of hexavalent chromium, have been used as corrosion inhibitors in corrosion-inhibiting coatings such as paints, sealants, and primers. However, chromates and other corrosion inhibitors generally have poor adhesion to metal substrates. Furthermore, there is regulatory pressure to eliminate the use of hexavalent chromium and other chromates in conversion coatings, primers, and manufacturing processes.

[0005] Traditionally, adhesive sol-gel films are placed at the interface between the metal substrate and the corrosion inhibitor to promote adhesion. However, adhesive sol-gels themselves do not have corrosion resistance. Therefore, over time, pores will form in the sol-gel that retain moisture, thereby promoting corrosion of the metal surface. It is desirable to try to incorporate corrosion inhibitors that lack chromate and other primers (such as aluminum primers) to improve the adhesion of the primer to the metal substrate or placed on the sol-gel while maintaining corrosion protection.

[0006] Therefore, there is a need in the art for a sol-gel having corrosion inhibiting capabilities that can maintain adequate adhesion to a metal substrate when coated with a primer coating. Summary of the Invention

[0007] The present disclosure relates to a coated substrate having a metal substrate and a sol-gel coating disposed on the metal substrate. The sol-gel coating includes from about 3 wt% to about 15 wt% of an organic corrosion inhibitor, based on the total sol-gel coating volume. The sol-gel includes a surfactant and the reaction product of an epoxy-containing organosilane, a metal alkoxide, and an acid.

[0008] The present disclosure also relates to a method for preparing a coated substrate. The method includes applying a sol-gel coating to a metal substrate to form a sol-gel coating. The sol-gel coating includes about 3 wt % to about 15 wt % of a corrosion inhibitor, based on the total sol-gel coating volume. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] For a detailed understanding of the above features of the present disclosure, reference may be made to some aspects shown in the accompanying drawings for a more particular description of the disclosure briefly summarized above. However, it should be noted that the accompanying drawings illustrate only typical aspects of the present disclosure and are therefore not to be considered limiting of its scope, as the present disclosure may admit to other equally effective aspects.

[0010] Figure 1 is a side view of a corrosion inhibiting sol-gel disposed on a substrate according to various aspects of the present disclosure.

[0011] Figure 2 is a schematic diagram of a method for preparing a coated substrate according to various aspects of the present disclosure.

[0012] Figure 3 is an illustrative potentiodynamic scan of a metal surface of a corrosion-resistant sol-gel according to various aspects of the present disclosure.

[0013] Figure 4 is an illustrative OPR current graph of a corrosion-resistant sol-gel according to various aspects of the present disclosure.

[0014] Figure 5 is an illustrative current-voltage graph of a corrosion-resistant sol-gel on an electrode surface according to various aspects of the present disclosure.

[0015] Figure 6A and 6B is a depiction of an SEM image of a corrosion-resistant sol-gel according to various aspects of the present disclosure. Figure 6A is a SEM image of a thin corrosion-resistant sol-gel. Figure 6B is a SEM image of a thick corrosion-resistant sol-gel.

[0016] Figure 7 is an illustrative corrosion-resistant sol-gel thickness graph of a corrosion-resistant sol-gel according to various aspects of the present disclosure.

[0017] Figure 8 is an illustrative corrosion-resistant sol-gel coating weight graph of corrosion-resistant sol-gels according to various aspects of the present disclosure.

[0018] Figure 9 is an illustrative absorption spectrum of a corrosion-resistant sol-gel according to various aspects of the present disclosure.

[0019] Figure 10 is an illustrative current-voltage graph of a corrosion-resistant sol-gel according to various aspects of the present disclosure.

[0020] Figure 11 Depicted are corrosion resistant sol-gels on bare 2024-T3 after 336 h, according to various aspects of the present disclosure.

[0021] Figure 12 is an illustrative impedance spectrum of a corrosion-resistant sol-gel according to various aspects of the present disclosure.

[0022] Figures 13A-13F is a depiction of substrates coated with corrosion resistant sol-gels according to various aspects of the present disclosure and a comparator after 2000 hours of ASTM B117 exposure. Figure 13A is the first substrate coated with the comparative after 2000 h of ASTM B117 exposure. Figure 13B The first substrate is coated with a first corrosion resistant sol-gel after 2000 hours of ASTM B117 exposure. Figure 13C The first substrate is coated with a second corrosion resistant sol-gel after 2000 hours of ASTM B117 exposure. Figure 13D is a second substrate coated with a comparative after 2000 h of ASTM B117 exposure. Figure 13E The second substrate was coated with the first corrosion resistant sol-gel after 2000 h of ASTM B117 exposure. Figure 13E The second substrate was coated with a second corrosion resistant sol-gel after 2000 h of ASTM B117 exposure.

[0023] Figures 14A-14C is a depiction of bare 7075-T6 panels coated with corrosion resistant sol-gels according to various aspects of the present disclosure and a comparator after 9 months of outdoor exposure. Figure 14A is bare 7075-T6 coated with a comparator. Figure 14B It is bare 7075-T6 coated with the first corrosion resistant sol-gel. Figure 14C is bare 7075-T6 coated with a second corrosion resistant sol-gel.

[0024] Figures 15A to 15F are depictions of bare Al 7075-T6 panels pretreated with comparative and corrosion resistant sol-gels with various primers according to various aspects of the present disclosure after exposure to an NSS chamber for 2000 h. Figure 15A Depicted are bare Al 7075-T6 panels pretreated with a comparative with rich Al Av-de. Figure 15B Depicted is a bare Al 7075-T6 panel with Al-rich Av-de pre-treated with a first corrosion resistant sol-gel. Figure 15C Depicted is a bare Al 7075-T6 panel with Al-rich Av-de pre-treated with a second corrosion resistant sol-gel. Figure 15D Depicted are bare Al 7075-T6 panels pretreated with a comparator with Akzo Nobel Aerodur 2118. Figure 15EDepicted is a bare Al 7075-T6 panel pretreated with a first corrosion resistant sol-gel with Akzo Nobel Aerodur 2118. Figure 15F Depicted is a bare Al 7075-T6 panel pretreated with a second corrosion resistant sol-gel with Akzo Nobel Aerodur 2118.

[0025] Figures 16A-16D is a depiction of bare 7075-T6 panels with Alodine 1200S as a pretreatment, various primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 16A Depicted are bare 7075-T6 panels primed with PPG RW 7171-64. Figure 16B Depicted is a bare 7075-T6 panel primed with Al-rich Av-dec. Figure 16C Depicted are bare 7075-T6 panels primed with Aerodur 2118. Figure 16D Depicted are bare 7075-T6 panels primed with PPG CA7231.

[0026] Figures 17A-17D is a depiction of bare 7075-T6 panels with Alodine 5900 as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 17A Depicted are bare 7075-T6 panels primed with PPG RW 7171-64. Figure 17B Depicted is a bare 7075-T6 panel primed with Al-rich Av-dec. Figure 17C Depicted are bare 7075-T6 panels primed with Aerodur 2118. Figure 20D Depicted are bare 7075-T6 panels primed with PPG CA7231.

[0027] Figures 18A-18D is a depiction of bare 7075-T6 panels with SurTec 650V as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 18A Depicted are bare 7075-T6 panels primed with PPG RW 7171-64. Figure 18B Depicted is a bare 7075-T6 panel primed with Al-rich Av-dec. Figure 18C Depicted are bare 7075-T6 panels primed with Aerodur 2118. Figure 18DDepicted are bare 7075-T6 panels primed with PPG CA7231.

[0028] Figures 19A-19D is a depiction of bare 7075-T6 panels with the corrosion resistant sol-gel of the present disclosure with DMCT as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 19A Depicted are bare 7075-T6 panels primed with PPG RW 7171-64. Figure 19B Depicted is a bare 7075-T6 panel primed with Al-rich Av-dec. Figure 19C Depicted are bare 7075-T6 panels primed with Aerodur 2118. Figure 19D Depicted are bare 7075-T6 panels primed with PPG CA7231.

[0029] Figures 20A-20D is a depiction of 7178 panels with Alodine 1200S as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 20A Depicted are bare 7178 panels primed with PPG RW 7171-64. Figure 20B Depicted is a bare 7178 panel primed with Al-rich Av-dec. Figure 20C Depicted are bare 7178 panels primed with Aerodur 2118. Figure 20D Depicted are bare 7178 panels primed with PPG CA7231.

[0030] Figures 21A-21C is a depiction of 7178 panels after 3000 hours of ASTM B117 testing with Alodine 5900 as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat in accordance with various aspects of the present disclosure. Figure 21A Depicted are bare 7178 panels primed with PPG RW 7171-64. Figure 21B Depicted is a bare 7178 panel primed with Al-rich Av-dec. Figure 21C Depicted are bare 7178 panels primed with Aerodur 2118.

[0031] Figures 22A-22C is a depiction of 7178 panels with SurTec 650V as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 22ADepicted are bare 7178 panels primed with PPG RW 7171-64. Figure 22B Depicted is a bare 7178 panel primed with Al-rich Av-dec. Figure 22C Depicted are bare 7178 panels primed with Aerodur 2118.

[0032] Figure 23A and 23B is a depiction of 7178 panels having the corrosion resistant sol-gel of the present disclosure with DMCT as a pretreatment, various non-chromate primers, and PPG 99GY001 polyurethane topcoat after 3000 hours of ASTM B117 testing in accordance with various aspects of the present disclosure. Figure 23A Depicted are bare 7178 panels primed with PPG RW 7171-64. Figure 23B Depicted is a bare 7178 panel primed with rich AlAv-dec.

[0033] Figure 24 is a comparative illustration of ranking 7075-T6 test panels that completed 3000 hours of exposure to an NSS chamber using various methods in accordance with various aspects of the present disclosure.

[0034] Figure 25 is a comparative illustration of ranking 7178 test panels that completed 2000 hours of exposure to an NSS chamber using various methods in accordance with various aspects of the present disclosure.

[0035] Figure 26 is a comparative illustration of rankings of 7075-T6 test panels exposed in an NSS chamber for 3000 hours and in an accelerated cycling chamber for 672 hours, according to various aspects of the present disclosure.

[0036] Figure 27 is a comparative illustration of rankings of 7178 test panels exposed in an NSS chamber for 3000 hours and in a cycling chamber for 672 hours, according to various aspects of the present disclosure. DETAILED DESCRIPTION

[0037] Various aspects of the present disclosure generally relate to corrosion-resistant sol-gels for aerospace applications. The sol-gels of the present disclosure include an epoxy-containing organosilane, a metal alkoxide, an acid stabilizer (or their reaction products), about 3 wt% to about 15 wt% of a corrosion inhibitor based on the total sol-gel coating volume, and a surfactant. It has been found that the surfactant present in the sol-gel prevents or reduces the porosity and blistering of the sol-gel / primer coating on the metal surface, thereby improving the corrosion inhibition ability of the sol-gel film because the accumulation of water in the sol-gel can be prevented or reduced. The surfactant can also improve the wettability of the coating on the metal surface, improving the coating adhesion and corrosion performance. In addition, it has been found that the use of an organic primer having a plurality of metal particles (e.g., aluminum, lithium, etc.) placed on the corrosion-resistant sol-gel can enhance the corrosion protection of alloys (e.g., aerospace alloys). The sol-gel of the present disclosure has corrosion inhibition ability, and the primer (placed on the sol-gel) can be a chrome-free primer or a chrome-containing primer.

[0038] The method of preparing a coated substrate of the present disclosure includes applying a sol-gel coating to a metal substrate to form a sol-gel coating. The sol-gel coating includes a corrosion inhibitor in an amount ranging from about 3 wt% of the corrosion inhibitor by volume of the sol-gel coating to about 15 wt% by volume of the sol-gel coating.

[0039] Metal substrate

[0040] The metal substrate comprises an aircraft metal surface, which may comprise steel or an alloy having a primary component such as aluminum. The metal substrate may comprise a primary component and a secondary component, referred to as an intermetallic compound. The intermetallic compound, for example, may contain copper metal, which is susceptible to corrosion. The metal substrate may comprise an aluminum substrate. The metal substrate may comprise an aluminum substrate with a copper intermetallic compound. As non-limiting examples, the metal substrate may be a 7075-T6 aluminum substrate or a 7178 aluminum substrate.

[0041] Sol-Gel

[0042] The term "sol-gel" is an abbreviation of solution-gelation and refers to a series of reactions in which a soluble metal species (usually a metal alkoxide or metal salt) hydrolyzes to form a metal hydroxide. The soluble metal species usually contains organic ligands that are suitable for corresponding to the resin in the bonded structure. The soluble metal species undergoes heterohydrolysis and heterocondensation reactions to form heterometallic bonds, such as Si-O-Zr. In the absence of organic acid, when the metal alkoxide is added to water, a white precipitate such as Zr(OH)2 quickly forms. Zr(OH)2 is insoluble in water, which hinders the formation of sol-gel. Acid is added to the metal alkoxide to form a water-based system. Depending on the reaction conditions, the metal polymer can condense into colloidal particles, or they can grow to form a network gel. The ratio of organic to inorganic matter in the polymer matrix is ​​controlled to maximize the performance for a specific application.

[0043] The thickness of the sol-gel is about 50 nm to about 4 μm, for example, about 100 nm to about 2.5 μm, such as about 100 nm, about 200 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 700 nm, about 800 nm, about 900 nm, about 1 μm, about 2 μm, about 2.5 μm, etc. The weight of the sol-gel is about 30 mg / ft 2 About 1000mg / ft 2 , for example, about 30 mg / ft 2 About 400mg / ft 2 , or about 250 mg / ft 2 About 1000mg / ft 2 , such as, for example, about 30 mg / ft 2 , about 100mg / ft 2 , about 200mg / ft 2 , about 300mg / ft 2 , about 400mg / ft 2 , about 500mg / ft 2 , about 600mg / ft 2 , about 700mg / ft 2 , about 800mg / ft 2 , about 900mg / ft 2 , about 1000mg / ft 2 wait.

[0044] Organosilanes

[0045] The weight fraction (wt %) of the organosilane in the sol-gel is from about 0.1 wt % to about 20 wt %, such as from about 0.3 wt % to about 15 wt %, such as from about 0.5 wt % to about 10 wt %, such as from about 0.7 wt % to about 5 wt %, such as from about 1 wt % to about 2 wt %, for example, about 1 wt %, about 1.5 wt %, about 2 wt %, based on the volume of the total sol-gel coating.

[0046] The organosilanes of the present disclosure are represented by formula (I):

[0047]

[0048] in:

[0049] R 2 、R 3 and R 4 Each independently is a straight chain or branched C 1-20 Alkyl. C 1-20 Alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl, and eicosyl;

[0050] R 1 Selected from alkyl, cycloalkyl, ether and aryl. Alkyl includes straight chain or branched C 1-20 Alkyl. C 1-20 Alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. Ethers include polyethylene glycol ethers, polypropylene glycol ethers, C1-C 20 Alkyl ethers, aryl ethers and cycloalkyl ethers.

[0051] Ethers are selected from:

[0052]

[0053]

[0054] wherein n is a positive integer. In at least one aspect, n is a positive integer and the ether has a number average molecular weight (Mn) of from about 300 to about 500, such as from about 375 to about 450, such as from about 400 to about 425.

[0055] The organosilane is a hydroxyl organosilane. Hydroxyl organosilane is substantially unreactive towards nucleophiles (e.g., some corrosion inhibitors). The hydroxyl organosilane of the present disclosure is represented by formula (II):

[0056]

[0057] Wherein R is selected from alkyl, cycloalkyl, ether and aryl. Alkyl includes straight chain or branched C 1-20 Alkyl. C 1-20 Alkyl groups include methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, octadecyl, nonadecyl and eicosyl. Ethers include polyethylene glycol ethers, polypropylene glycol ethers, C1-C 20 Alkyl ethers, aryl ethers and cycloalkyl ethers.

[0058] Ethers are selected from:

[0059]

[0060] wherein n is a positive integer. In at least one aspect, n is a positive integer and the ether has a number average molecular weight (Mn) of from about 300 to about 500, such as from about 375 to about 450, such as from about 400 to about 425.

[0061] Organosilane is represented by Compound 1 or Compound 2:

[0062]

[0063] The organosilane is selected from 3-aminopropyltriethoxysilane, 3-glycidoxy-propyltriethoxysilane, p-aminophenyltrimethoxysilane, p-aminophenyltriethoxysilane, allyltrimethoxysilane, allyltriethoxysilane, n-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-glycidoxypropyldiisopropylethoxysilane, (3-glycidoxypropyl)methyldiethoxysilane, 3-glycidoxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methyl Acryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, n-phenylaminopropyltrimethoxysilane, vinylmethyldiethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, bis(trimethoxysilyl)ethane, bis(triethoxysilyl)ethane, bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]disulfide, bis[3-(trimethoxysilyl)propyl]disulfide, bis[3-(triethoxysilyl)propyl]trisulfide, bis[3-(trimethoxysilyl)propyl]trisulfide, bis[3-(trimethoxysilyl)propyl]tetrasulfide and bis[3-(trimethoxysilyl)propyl]tetrasulfide.

[0064] The organosilanes useful in forming the sol-gels of the present disclosure provide electrophilic silicon and / or epoxide moieties that can react with nucleophiles, such as hydroxyl-containing nucleophiles. The organosilanes of the present disclosure provide sol-gels with reduced porosity and foaming compared to conventional sol-gels.

[0065] Metal alkoxides

[0066] The metal alkoxide that can be used to form the sol-gel of the present disclosure provides the metal atom coordinated in the sol-gel for adhesion and mechanical strength.The metal alkoxide of the present disclosure includes at least one of zirconium alkoxide, titanium alkoxide, hafnium alkoxide, yttrium alkoxide, cerium alkoxide and lanthanum alkoxide.The metal alkoxide can have four alkoxy ligands coordinated with the metal having an oxidation number of +4.The limiting examples of metal alkoxide are tetramethoxy zirconium (IV), tetraethoxy zirconium (IV), four n-propoxy zirconium (IV), tetraisopropoxy zirconium (IV), four n-butoxy zirconium (IV), tetraisobutoxy zirconium (IV), four n-pentoxy zirconium (IV), four isopentoxy zirconium (IV), four n-hexoxy zirconium (IV), four isohexoxy zirconium (IV), four n-heptoxy zirconium (IV), four isoheptoxy zirconium (IV), four n-octoxy zirconium (IV), four isooctoxy zirconium (IV), four n-nonoxy zirconium (IV), four isononoxy zirconium (IV), four n-decoxy zirconium (IV) and four isodecoxy zirconium (IV).

[0067] The sol-gel includes a metal alkoxide content, wherein the metal alkoxide content is a metal alkoxide reaction product formed in the sol-gel. The weight fraction (wt %) of the metal alkoxide content by volume in the total sol-gel coating is from about 0.1 wt % to about 10 wt %, such as from about 0.2 wt % to about 5 wt %, such as from about 0.3 wt % to about 3 wt %, such as from about 0.4 wt % to about 2 wt %, such as from about 0.5 wt % to about 1 wt %, for example, about 0.2 wt %, about 0.5 wt %, about 1 wt %.

[0068] Acid stabilizer

[0069] The acid stabilizer used to form the sol-gel of the present disclosure provides stability to the metal alkoxide and corrosion inhibitor of the sol-gel and reduces the pH of the sol-gel. The pH of the sol-gel (and the components that form the sol-gel) can be controlled by using an acid stabilizer. Acid stabilizers of the present disclosure include organic acids. Organic acids include acetic acid (such as glacial acetic acid) or citric acid. Acid stabilizers with lower acidity (e.g., pKa greater than that of acetic acid) such as glycols, ethoxyethanol, or H2NCH2CH2OH can also be used.

[0070] The pH of the sol-gel of the present disclosure is from about 2 to about 5, such as from about 3 to about 4. The weight fraction (wt%) of the acid stabilizer by volume in the total sol-gel is from about 0.1 wt% to about 10 wt%, such as from about 0.2 wt% to about 5 wt%, such as from about 0.3 wt% to about 3 wt%, such as from about 0.4 wt% to about 2 wt%, such as from about 0.5 wt% to about 1 wt%, for example, about 0.1 wt%, about 0.2 wt%, about 0.3 wt%, about 0.4 wt%, about 0.5 wt%. For example, but not limited to, the wt% of the acid stabilizer in the sol-gel is about 0.5 wt%, and the weight fraction of the metal alkoxide is about 0.6 wt% or greater. As a further non-limiting example, the wt% of the acid stabilizer in the sol-gel is about 0.3 wt%, and the weight fraction of the metal alkoxide is less than 0.6 wt%.

[0071] The ratio of metal alkoxide to acid stabilizer in the sol-gel can be from about 1:1 to about 3:1, such as about 2: 1. The molar ratio of acid stabilizer to metal alkoxide can be from about 1:1 to about 40:1, such as from about 3:1 to about 8:1, such as from about 4:1 to about 6:1, such as from about 4:1 to about 5:1.

[0072] Without being bound by theory, it is believed that these proportions of acid stabilizer not only help stabilize the metal alkoxide for hydrolysis, but also protonate the mercaptan portion of the corrosion inhibitor, thereby reducing or preventing reaction of the corrosion inhibitor with, for example, the metal alkoxide.

[0073] surfactants

[0074] Without wishing to be bound by theory, surfactants useful in forming the sol-gels of the present disclosure enhance the adhesion of the sol-gel to the metal substrate by increasing the surface wettability of the coating on the metal surface. Surfactants can enhance adhesion, and this is quantified according to wet cross hatch adhesion in accordance with ASTM D3359. For example, and without limitation, a sol-gel with a surfactant can increase wet cross hatch adhesion to a value of 10.

[0075] Without wishing to be bound by theory, the surfactants that can be used to form the sol-gel of the present disclosure provide enhanced adhesion of the sol-gel to the primer. The surfactants of the present disclosure can include surfactants that can undergo an alkoxylation reaction, wherein addition of an epoxide to the substrate occurs. The surfactant can include one or more alcohol ethoxylates, alcohol propoxylates, ethoxysulfates, polyethoxylated amines, and the like. For example, but not limited to, the surfactant can be ethylene-oxide alcohol, propylene-oxide alcohol, ethylene-oxide-propylene-oxide alcohol, polyethoxylated tallow amine, ethanolamine, diethanolamine, triethanolamine, and the like.

[0076] Corrosion inhibitors

[0077] The corrosion inhibitors that can be used to form the sol-gels of the present disclosure provide corrosion resistance (to water) to a metal substrate placed adjacent to the sol-gel. The corrosion inhibitors of the present disclosure are compounds having one or more thiol moieties. Aircraft metal surfaces can include steel or alloys having a primary component such as aluminum and a secondary component known as an intermetallic compound. Intermetallic compounds, for example, typically contain copper metal, which is susceptible to corrosion. Without being bound by theory, the interaction of the thiol moiety of the corrosion inhibitors of the present disclosure with the copper-containing intermetallic compound on the metal surface (such as the aluminum alloy surface) prevents corrosion of the metal surface. More specifically, the interaction of the thiol moiety of the corrosion inhibitors of the present disclosure with the intermetallic compound prevents the reduction of the intermetallic compound by slowing the rate of oxygen reduction and reducing the oxidation of the metal alloy (such as the aluminum alloy).

[0078] The corrosion inhibitors of the present disclosure are organic compounds that include disulfide groups and / or thiol groups (e.g., metal-sulfide bonds). For example, the corrosion inhibitor is not an organometallic corrosion inhibitor. The corrosion inhibitor is represented by the formula R 1 --S n --X--R 2 Indicates that R 1 is an organic group, n is an integer greater than or equal to 1, X is a sulfur or metal atom, and R 2 is an organic group. 1 and R 2 One or both of the compounds may include additional polysulfide groups and / or thiol groups. In addition, the corrosion inhibitor includes a compound having the formula -(R 1 --S n --X--R 2 ) q -polymers wherein R 1is an organic group, n is a positive integer, X is a sulfur or metal atom, R 2 is an organic group, and q is a positive integer. (of a polymeric or monomeric corrosion inhibitor) R 1 and R 2 R is independently selected from H, alkyl, cycloalkyl, aryl, thiol, polysulfide or thione. 1 and R 2 Each of R may be independently substituted with a moiety selected from alkyl, amino, phosphorus-containing, ether, alkoxy, hydroxyl, sulfur-containing, selenium, or tellurium. 1 and R 2 Each has 1 to 24 carbon atoms and / or non-hydrogen atoms. For example, R 1 and R 2 Examples of heterocyclic groups include azole, triazole, thiazole, dithiazole and / or thiadiazole.

[0079] Corrosion inhibitors include metals in metal thiolate complexes. The corrosion inhibitor may include a metal center and one or more thiol groups (ligands) bound and / or coordinated to the metal center via metal-sulfide bonds. Thiolates are derivatives of thiols in which a metal atom replaces the hydrogen bonded to the sulfur. Thiolates have the general formula MSR 1 , where M is the metal, and R 1 is an organic group. 1 The metal thiolate complex has the general formula M-(SR 1 ) n , wherein n is generally an integer from 2 to 9, and M is a metal atom. The metal is copper, zinc, zirconium, aluminum, iron, cadmium, lead, mercury, silver, platinum, palladium, gold and / or cobalt.

[0080] Corrosion inhibitors include azole compounds. Examples of suitable azole compounds include cyclic compounds having one nitrogen atom, such as pyrrole, cyclic compounds having two or more nitrogen atoms, such as pyrazole, imidazole, triazole, tetrazole, and pentazole, cyclic compounds having one nitrogen atom and one oxygen atom, such as oxazole and isoxazole, and cyclic compounds having one nitrogen atom and one sulfur atom, such as thiazole and isothiazole. Non-limiting examples of suitable azole compounds include 2,5-dimercapto-1,3,4-thiadiazole, 1H-benzotriazole, 1H-1,2,3-triazole, 2-amino-5-mercapto-1,3,4-thiadiazole, also known as 5-amino-1,3,4-thiadiazole-2-thiol, 2-amino-1,3,4-thiadiazole. For example, but not limited to, the azole can be 2,5-dimercapto-1,3,4-thiadiazole. The azole may be present in the composition at a concentration of 0.01 g / L to 1 g / L of the sol-gel composition, such as 0.4 g / L of the sol-gel composition.The azole compound may include benzotriazole and / or 2,5-dimercapto-1,3,4-thiadiazole.

[0081] The corrosion inhibitors disclosed herein include heterocyclic thiols and amines that can eliminate oxygen reduction. The heterocyclic thiols include thiadiazoles having one or more thiol moieties. Non-limiting examples of thiadiazoles having one or more thiol moieties include 1,3,4-thiadiazole-2,5-dithiol and thiadiazoles represented by formula (III) or formula (IV):

[0082]

[0083] Thiadiazoles of formula (III) are commercially available from Vanderbilt Chemicals, LLC, located in Norwalk, Connecticut, and are known as 829. Thiadiazoles of formula (IV) are commercially available from WPC Technologies, Inc. TM (located in Oak Creek, Wisconsin) and is called InhibiCor TM 1000.

[0084] The corrosion inhibitors of the present disclosure may be derivatives of 2,5-dimercapto-1,3,4-thiadiazole represented by HS-CN2SC-SH or "DMTD", and selected derivatives of trithiocyanate ("TMT") used as corrosion inhibitors in relation to paints. Examples include 2,5-dimercapto-1,3,4-thiadiazole (DMTD), 2,4-dimercapto-s-triazolo[4,3-b]-1,3-4-thiadiazole and trithiocyanate (TMT). Other examples include N-, S- and N,N-, S,S- and N,S-substituted derivatives of DMTD, such as 5-mercapto-3-phenyl-1,3,4-thiadiazolidine-2-thione or bismuthol II (3-phenyl-1,3,4-thiadiazolidine-2,5-dithione) and various S-substituted derivatives of trithiocyanate. Other examples include 5,5'-dithiobis(1,3,4-thiadiazole-2(3H)-thione or (DMTD)2, or (DMTD), polymers of DMTD; 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione; or (TMT)2, dimers and polymers of TMT. Other examples include the general formula M(DMTD) nDMTD salts, wherein n = 1, 2 or 3, and M is a metal cation, such as M = Zn(II), Bi(III), Co(II), Ni(II), Cd(II), Pb(II), Ag(I), Sb(III), Sn(II), Fe(II) or Cu(II) (for example: ZnDMTD, Zn(DMTD)2, Bi(DMTD)3); similar salts of TMT, such as ZnTMT in a 1:1 ratio; and comparable soluble Li(I), Ca(II), Sr(II), Mg(II), La(III), Ce(III), Pr(III) or Zr(IV) salts. Additional examples include salts of the general formula M[(DMTD) n ] m (DMTD) n Salts of wherein n=2 or n>2, M=1, 2 or 3, and M is a metal cation, such as M=Zn(II), Bi(III), Co(II), Ni(II), Cd(II), Pb(II), Ag(I), Sb(III), Sn(II), Fe(II) or Cu(II). Typical examples are: Zn[(DMTD)2], Zn[(DMTD)2]2.

[0085] Additional examples include DMTD, (DMTD) n or an ammonium, arylammonium or alkylammonium salt of 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione or 2,4-dimercapto-s-triazolo[4,3-b]-1,3,4-thiadiazole. Typical examples include: cyclohexylamine:DMTD in ratios of 1:1 and 2:1; dicyclohexylamine:DMTD in ratios of 1:1 and 2:1; aniline:DMTD in ratios of 1:1 and 2:1; similar salts of TMT, such as dicyclohexylamine:TMT in a ratio of 1:1. Further examples include DMTD or (DMTD) formed from polyamines n and polyammonium salts of TMT.

[0086] Additional examples include naturally conductive polyaniline doped with DMTD or (DMTD)2 or 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione and TMT; naturally conductive polypyrrole and / or polythiophene doped with DMTD, (DMTD)2 and 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione and / or TMT.

[0087] Additional examples include micro- or nanocomposites of polyDMTD / polyaniline, polyDMTD / polypyrrole, and polyDMTD / / polythiophene; similar micro- or nanocomposites with TMT; and similar micro- or nanocomposites with 5,5'-thiobis(1,3,4-thiadiazole-2(3H)-thione; DMTD or salts of DMTD or derivatives of DMTD and TMT as organic components of various pigment-grade inorganic matrices or physical mixtures. Such inorganic matrices may include non-toxic anionic and cationic species having corrosion inhibitor properties, such as MoO4 - PO4 - 、HPO3 - , polyphosphate, BO2 - 、SiO4 - 、NCN - WO4 - , phosphomolybdate, phosphotungstate, and, respectively, Mg, Ca, Sr, La, Ce, Zn, Fe, Al, Bi.

[0088] Further examples include encapsulated forms of DMTD or salts of DMTD or derivatives of DMTD and TMT, such as inclusion compounds in various polymer matrices, or as cyclodextrin inclusion compounds or microencapsulated forms.

[0089] Pigmentary forms of DMTD include Zn(DMTD)2 and Zn-DMTD (as well as other organic and inorganic salts of the former) with inorganic products or corrosion inhibitor pigments such as: phosphates, molybdates, borates, silicates, tungstates, phosphotungstates, phosphomolybdates, cyanamides or carbonates of the previously specified cationic species, as well as oxides. Examples include: zinc phosphate, cerium molybdate, calcium silicate, strontium borate, zinc cyanamide, cerium phosphotungstate, ZnO, CeO2, ZrO2 and amorphous SiO2.

[0090] The corrosion inhibitor is a lithium ion and a counterion, which may include various ions known to form salts with lithium. Non-limiting examples of counterions suitable for forming salts with lithium include carbonates, hydroxides, and silicates (e.g., orthosilicates and metasilicates). For example, the corrosion inhibitor includes a lithium carbonate salt, a lithium hydroxide salt, or a lithium silicate salt (e.g., lithium orthosilicate salt or lithium metasilicate salt). The counterion includes various ions known to form salts with other Group IA (or Group 1) metals (e.g., Na, K, Rb, Cs, and / or Fr). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonates, hydroxides, and silicates (e.g., orthosilicates and metasilicates). For example, but not limited to, the corrosion inhibitor includes an alkali metal carbonate, an alkali metal hydroxide salt, and / or an alkali metal silicate (e.g., alkali metal orthosilicates or alkali metal metasilicates). For example, some non-limiting examples of suitable salts include carbonates, hydroxides, and silicates (eg, orthosilicates or metasilicates) of sodium, potassium, rubidium, cesium, and rubidium.

[0091] The corrosion inhibitors disclosed herein include aluminum- and magnesium-rich compounds that can provide cathodic protection of materials. The aluminum-rich corrosion inhibitor includes aluminum or an aluminum alloy, wherein the aluminum or aluminum alloy comprises more than 50 wt% by volume of the corrosion inhibitor. The magnesium-rich corrosion inhibitor includes magnesium or a magnesium alloy, wherein the magnesium or magnesium alloy comprises more than 50 wt% by volume of the corrosion inhibitor. The corrosion inhibitors disclosed herein can include cesium compounds.

[0092] In the total sol-gel, the weight fraction (wt %) of the corrosion inhibitor is from about 1 wt % to about 15 wt %, such as from about 3 wt % to about 15 wt %, such as from about 1 wt % to about 5 wt %, such as from about 5 wt % to about 10 wt %, such as from about 10 wt % to about 15 wt %, such as from about 12 wt % to about 15 wt %, for example, about 1 wt %, about 5 wt %, about 10 wt %, about 15 wt %. For example, but not limited to, the wt % of the corrosion inhibitor in the total sol-gel is from about 3 wt % to about 15 wt % by volume, and the weight fraction of the metal alkoxide in the total sol-gel is about 0.6 wt % or greater by volume. As a further non-limiting example, the wt % of the acid stabilizer in the total sol-gel is from about 3 wt % to about 15 wt %, and the weight fraction of the metal alkoxide in the sol-gel is less than 0.6 wt % by volume of the total sol-gel. The corrosion inhibitors incorporated into the sol-gel provide an additional layer of corrosion protection near the metal surface. Furthermore, this will improve corrosion protection when used over a non-chromated primer coating.

[0093] Primer

[0094] The primer of the present disclosure can be placed over the sol-gel coating to enhance bonding adhesion to the aluminum surface and adhesion to a subsequent epoxy primer. The primer of the present disclosure can be composed of a reactive polymer. For example, the primer can be composed of an epoxy resin, such as an amine-cured epoxy resin. The primer of the present disclosure can be composed of a siloxane, such as a polysiloxane. The primer of the present disclosure can include from about 0 to about 30 wt% by volume of a corrosion inhibitor in the primer solution.

[0095] The primer of the present disclosure includes an organic primer having a plurality of metal particles that can prevent corrosion and filiform corrosion caused by fasteners. The metal particles can sacrifice corrosion and inhibit the corrosion of the surface metal by undergoing oxidation before the surface metal. The metal particles can include aluminum ions and counterions, and the counterions can include various ions known to form salts with aluminum. Non-limiting examples of counterions suitable for forming salts with aluminum include carbonate, hydroxide and silicate (e.g., orthosilicate and metasilicate). For example, but not limited to, counterions include aluminum carbonate, aluminum hydroxide or aluminum silicate (e.g., orthosilicate or metasilicate). Counterions can include various ions known to form salts with other Group 13 metals (e.g., B, Ga, In, Tl, Ho and / or Es). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide and silicate (e.g., orthosilicate and metasilicate).

[0096] The metal particles may include magnesium ions and counterions, and the counterions may include various ions known to form salts with magnesium. Non-limiting examples of counterions suitable for forming salts with magnesium include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate). For example, but not limited to, corrosion inhibitors include magnesium carbonate, magnesium hydroxide, or magnesium silicate (e.g., orthosilicate or metasilicate). Counterions may include various ions known to form salts with other Group 2 metals (e.g., Be, Ca, Sr, Ba, and / or Ra). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate).

[0097] The metal particles may include lithium ions and counterions, and the counterions may include various ions known to form salts with lithium. Non-limiting examples of counterions suitable for forming salts with lithium include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate). For example, but not limited to, corrosion inhibitors include lithium carbonate, lithium hydroxide, or lithium silicate (e.g., lithium orthosilicate or metasilicate). Counterions may include various ions known to form salts with other Group IA (or Group 1) metals (e.g., Na, K, Rb, Cs, and / or Fr). Non-limiting examples of counterions suitable for forming salts with alkali metals include carbonate, hydroxide, and silicate (e.g., orthosilicate and metasilicate).

[0098] The thickness of the primer coating (placed over the sol-gel) is from about 0.3 mil to about 2.5 mils, for example from about 1.0 mil to about 2.0 mils, such as about 0.3 mil, about 0.5 mil, about 1.0 mil, about 1.5 mil, about 2.0 mil, about 2.5 mils, etc.

[0099] Topcoat

[0100] A topcoat of the present invention can be placed over a primer coating to form a sol-gel of the present invention that has the corrosion resistance (to water) of a metal substrate to which the sol-gel is adjacent. The topcoat can include an organic topcoat, such as a polymer coating (e.g., an epoxy coating and / or a urethane coating), a polymeric material, a composite material (e.g., a filled composite material and / or a fiber-reinforced composite material), a laminate, or a mixture thereof. The topcoat includes at least one of a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a lacquer, a polyurethane, a polyester, or a combination thereof. For example, but not limited to, the topcoat is a polyurethane. The polyurethane topcoat prevents water from penetrating the coating, thereby enhancing corrosion protection. The topcoat has a thickness of about 2 mils to about 3 mils, for example, about 2.1 mils to about 2.9 mils, such as about 2 mils, about 2.1 mils, about 2.2 mils, about 2.3 mils, about 2.4 mils, about 2.5 mils, about 2.6 mils, about 2.7 mils, about 2.8 mils, about 2.9 mils, about 3 mils, etc. For example, but not limitation, the topcoat has a thickness of about 2 mils to about 3 mils, and the primer has a thickness of about 0.3 mils to about 2.5 mils.

[0101] Sol-gel system

[0102] Figure 1 is a side view of a corrosion-inhibiting sol-gel disposed on a substrate. Corrosion-inhibiting sol-gel system 100 includes a sol-gel 102 disposed on a material substrate 104. Sol-gel 102 has corrosion-inhibiting properties that provide corrosion protection for material substrate 104. Sol-gel 102 promotes adhesion between metal substrate 104 and a second layer 106. Second layer 106 can be a sealant, adhesive, primer, or coating that can be disposed on sol-gel 102 by, for example, spray drying.

[0103] The material substrate 104 can be any suitable material described herein and / or can include any suitable structure that benefits from the sol-gel 102 placed thereon. The material substrate 104 can define one or more components (such as structural or mechanical components) of an environmentally exposed device, such as an aircraft, a watercraft, a spacecraft, a land vehicle, equipment, a civil structure, a fastener, a wind turbine, and / or other devices susceptible to environmental degradation. The material substrate 104 can be part of a larger structure, such as a vehicle component. A vehicle component is any suitable component of a vehicle, such as a structural component, such as an aircraft's landing gear, a panel, or a joint. Examples of vehicle components include rotor blades, landing gear, an auxiliary power unit, an aircraft nose, a fuel tank, a tail cone, a panel, a coating overlap between two or more panels, a wing to fuselage assembly, a structural aircraft composite, a fuselage joint, a wing rib to skin joint, and / or other internal components. The material substrate 104 can be made of at least one of aluminum, aluminum alloy, magnesium, magnesium alloy, nickel, iron, iron alloy, steel, titanium, titanium alloy, copper and copper alloy, as well as glass / silicon dioxide and other inorganic or mineral substrates. The material substrate 104 is made of steel. The material substrate 104 can be a 'bare' substrate, with no coating (unplated metal), conversion coating and / or corrosion protection between the material substrate 104 and the sol-gel 102. Additionally or optionally, the material substrate 104 can include surface oxidation and / or hydroxylation. Therefore, the sol-gel 102 can be directly bonded to the material substrate 104 and / or the surface oxide layer on the surface of the material substrate 104. The material is not sensitive to water, but the sol-gel placed on the material can protect other adjacent structures that may be sensitive to water.

[0104] The second layer 106 is disposed on a second surface 110 of the sol-gel 102 opposite the first surface 108 of the sol-gel 102. The thickness of the sol-gel 102 is less than the thickness of the material substrate 104. The thickness of the sol-gel 102 is about 50 nm to about 4 μm, for example, about 100 nm to about 2.5 μm, such as about 100 nm, about 200 nm, about 300 nm, about 400 nm, about 500 nm, about 600 nm, about 700 nm, about 800 nm, about 900 nm, about 1 μm, about 2 μm, about 2.5 μm, etc. Thinner coatings may have fewer defects (are more likely to be defect-free), while thicker coatings may provide more wear, electrical, and / or thermal protection to the underlying material substrate 104.

[0105] The second layer 106 includes an organic material (e.g., an organic chemical composition) configured to bond and / or adhere to the sol-gel 102. The second layer 106 includes a paint, a primer, a topcoat, a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber-reinforced composite material), a laminate, or a mixture thereof. The second layer 106 includes at least one of a polymer, a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a lacquer, a polyurethane, and a polyester. The second layer 106 may additionally include at least one of a pigment, a binder, a surfactant, a diluent, a solvent, a particle (e.g., a mineral filler), a corrosion inhibitor, and a fiber (e.g., carbon, aramid, and / or glass fiber).

[0106] The third layer 112 is disposed on a proximal surface 114 of the second layer 106 opposite the second surface 110 of the sol-gel 102. The third layer 112 includes an organic material (e.g., an organic chemical composition) configured to bond and / or adhere to the second layer 106. The third layer 112 includes a paint, a primer, a topcoat, a polymer coating (e.g., an epoxy coating and / or a polyurethane coating), a polymer material, a composite material (e.g., a filled composite material and / or a fiber-reinforced composite material), a laminate, or a mixture thereof. The third layer 112 includes at least one of a polymer, a resin, a thermosetting polymer, a thermoplastic polymer, an epoxy resin, a lacquer, a polyurethane, and a polyester. The third layer 112 may additionally include at least one of a pigment, a binder, a surfactant, a diluent, a solvent, a particle (e.g., a mineral filler), a corrosion inhibitor, and a fiber (e.g., carbon, aramid, and / or glass fiber).

[0107] Sol-gel formation method

[0108] The method for forming the sol-gel of the present invention comprises mixing a metal alkoxide, acetic acid and an organic solvent, such as an anhydrous organic solvent, and then stirring for about 1 minute to about 1 hour, such as about 30 minutes. Then, another organic solvent (for example, about 1 vol% to 20 vol% of organic solvent relative to the total volume, such as 5 vol%) is added to the metal alkoxide / acetic acid mixture. Then, an organosilane is added to the mixture and stirred for about 1 minute to about 1 hour, such as about 30 minutes. A corrosion inhibitor is added to the mixture in an amount of about 3 wt% of the corrosion inhibitor relative to the mixture to about 15 wt% of the corrosion inhibitor relative to the mixture. The mixture can be placed on a material substrate. The placed mixture can be cured at ambient temperature or heated to increase the rate of curing / sol-gel formation.

[0109] Figure 2 is a flow chart illustrating a method 200 of forming a sol-gel 102. Figure 2As shown, the sol-gel 102 can be formed by mixing 202 one or more sol-gel components. The sol-gel components include two or more of an organosilane, a metal alkoxide, an acid stabilizer, and a corrosion inhibitor, wherein the corrosion inhibitor is present in an amount ranging from about 3 wt% of the corrosion inhibitor relative to the sol-gel to about 15 wt% of the corrosion inhibitor relative to the sol-gel. The mixed components are cured 208 to form the sol-gel 102.

[0110] Typically, mixing 202 is performed by dispersing (eg, emulsifying, suspending, and / or dissolving) the components of the sol-gel formulation in an organic solvent, preferably an anhydrous organic solvent, and optionally stirring the sol-gel formulation.

[0111] Mixing 202 includes mixing the sol-gel components to form a mixture (e.g., a solution, a mixture, an emulsion, a suspension, and / or a colloid). Mixing 202 includes mixing all of the sol-gel components simultaneously. Alternatively, mixing 202 includes mixing any two components (e.g., a metal alkoxide and an acid stabilizer in an organic solvent) to form a first mixture, and then mixing the remaining components into the first mixture to form a second mixture. The first mixture and the second mixture each have a moisture content of about 0.1 wt % water relative to the mixture to about 10 wt % water relative to the mixture, such as from about 0.1 wt % to about 5 wt %, such as from about 0.1 wt % to about 3 wt %, such as from about 0.1 wt % to about 1 wt %, such as about 0.1 wt % to about 0.5 wt %, such as 0.5 wt % or less, such as 0.3 wt % or less, such as 0.1 wt % or less, such as 0 wt %.

[0112] Mixing 202 can include dissolving, suspending, emulsifying, and / or dispersing the sol-gel components in an organic solvent prior to mixing with one or more other sol-gel components. Examples of solvents for dissolving, suspending, emulsifying, and / or dispersing the sol-gel components include one or more of alcohols (e.g., ethanol or propanol), ethylene glycol, propylene glycol, polyethylene glycol, polypropylene glycol, ethers (e.g., dimethyl ether or dipropylene glycol dimethyl ether), glycol ethers, tetrahydrofuran (THF), N-methyl-2-pyrrolidone (NMP), and dimethyl sulfoxide (DMSO).

[0113] Additionally or alternatively, mixing 202 can include mixing one or more sol-gel components in the form of solids, aggregates, and / or powders with one or more other sol-gel ingredients. For example, where mixing 202 includes mixing solids, powders, and / or viscous liquids, mixing 202 can include mixing with a high shear mixer (e.g., a paint shaker or a planetary centrifugal mixer or a stirrer). High shear mixers facilitate crushing and / or finely dispersing solids to form a substantially uniform mixture. For example, high shear mixers can dissolve, suspend, emulsify, disperse, homogenize, depolymerize, and / or decompose solids into a sol-gel formulation.

[0114] The sol-gel components may be diluted during mixing 202 to control the self-condensation reaction, thereby increasing the pot life of the mixed sol-gel formulation. Mixing 202 may include forming the weight percentage (wt %) of the mixture (metal alkoxide + organosilane + acid stabilizer relative to the mixture) to be about 0.1 wt % to about 30 wt %, such as from about 0.3 wt % to about 20 wt %, such as from about 1 wt % to about 10 wt %, such as from about 1 wt % to about 5 wt %, such as from about 2 wt % to about 4 wt %, such as from about 2 wt % to about 3 wt %, for example, about 1 wt %, about 1.5 wt %, about 2 wt %, about 2.5 wt %, about 3 wt %.

[0115] Mixing 202 can include forming a weight percentage (wt %) of the corrosion inhibitor by volume in the mixture from about 0.1 wt % to about 50 wt %, such as from about 0.2 wt % to about 40 wt %, such as from about 0.5 wt % to about 35 wt %, such as from about 1 wt % to about 30 wt %, such as from about 2 wt % to about 25 wt %, such as from about 3 wt % to about 15 wt %, for example, about 4 wt %, about 5 wt %, about 7 wt %, about 10 wt %, about 15 wt %. The sol-gel formulation includes a corrosion inhibitor, and mixing 202 includes forming the weight percentage (wt %) of the mixture (metal alkoxide + organosilane + acid stabilizer relative to the mixture) to be from about 0.3 wt % to about 50 wt %, such as from about 1 wt % to about 45 wt %, such as from about 2 wt % to about 40 wt %, such as from about 3 wt % to about 35 wt %, such as from about 4 wt % to about 25 wt %, such as from about 8 wt % to about 22 wt %, for example, about 10 wt %, about 12 wt %, about 15 wt %.

[0116] During mixing 202, the volume ratio of organosilane to metal alkoxide in the sol-gel formulation is from about 5% to about 20%, for example, about 9% to about 11%, wherein the metal alkoxide has been pre-treated with an acid. For example, but not limited to, the volume ratio of organosilane to metal alkoxide is about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, etc. Higher ratios increase the % solids in the sol-gel coating and allow for mixing higher concentrations of inhibitor into the coating.

[0117] During mixing 202, the corrosion inhibitor can be mixed so that 90% of the total particles (D90) in the mixture have a diameter of less than about 2 μm to about 5 μm, such as about 2 μm, about 3 μm, about 4 μm, or about 5 μm. The smaller particle size allows the corrosion inhibitor to be uniformly mixed in the mixture. Particle size mentioned herein can refer to an average particle size. The average particle size can be determined in commercially available products or by laser scattering according to various methods (e.g., ISO 4406).

[0118] The mixture of sol-gel components can be incubated 204 for a period of time, for example, from about 1 minute to about 60 minutes, such as from about 5 minutes to about 30 minutes, such as from about 10 minutes to about 20 minutes. In addition, the pot life is the time period from mixing to forming the sol-gel (for example, the mixture becomes too viscous to be used). The pot life can be from about 1 hour to about 24 hours, such as from about 2 hours to about 8 hours, such as about 4 hours. Incubation 204 can be carried out under ambient conditions (for example, at room temperature) and / or at high temperature. Suitable incubation temperatures include about 10°C to about 100°C, such as from about 20°C to about 70°C, such as from about 30°C to about 50°C, for example, about 40°C.

[0119] Method 200 includes coating 206 a material substrate 104 with a mixture comprising a sol-gel component and incubating 204 the mixture. Incubating 204 includes allowing the mixture comprising the sol-gel component to stand at room temperature for about 30 minutes or longer after mixing the mixture comprising the sol-gel component. Coating 206 can include wetting the material substrate 104 with the mixture comprising the sol-gel component, for example, by spraying, dipping, brushing, and / or wiping the mixture comprising the sol-gel component onto the material substrate 104. For example, suitable spraying methods include spraying with a spray gun, spraying with a high-volume, low-pressure spray gun, and / or spraying with a hand pump sprayer. The mixture comprising the sol-gel component is allowed to drain from the wet material substrate 104 for several minutes (e.g., 1-30 minutes, 1-10 minutes, or 3-10 minutes) and, if necessary, any excess undried mixture can be removed by suction from the material substrate 104 and / or gently blown out of the material substrate 104 with compressed air.

[0120] Coating 206 includes cleaning and / or pre-treating the material substrate 104 before wetting the material substrate 104 with the mixture including the sol-gel component. Before applying the sol-gel coating, the metal substrate can be pre-treated by immersing it in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH. The solution can include about 3 g / L to 22 g / L of a water-soluble trivalent chromium salt, about 1.5 g / L to 11.5 g / L of an alkali metal hexafluorozirconate, about 0 g / L (e.g., 0.1 g / L) to 10 g / L of a water-soluble thickener, and about 0 g / L (e.g., 0.1 g / L) to 10 g / L of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and combinations thereof.

[0121] In general, the sol-gel 102 adheres and / or bonds well to clean, bare material substrates that are substantially free of dirt, non-reactive surface oxides, and / or corrosion products, and preferably have a sufficient concentration of reactive hydroxyl groups or other chemically reactive species. Surface preparation methods for the material substrate may include degreasing, alkaline cleaning, chemical etching, chemical deoxidation, mechanical deoxidation (e.g., sanding and / or grinding), and / or other suitable methods for producing a sol-gel compatible surface. Coating 206 typically does not include coating the metal substrate 104 with an undercoat or forming a chemical conversion coating on the metal substrate 104, unless the coating is applied to produce a hydroxyl-rich substrate or otherwise improve compatibility with the sol-gel. The surface of the material substrate can be made hydroxyl-rich by placing a hydroxy silicate on the material surface.

[0122] The method of the present disclosure comprises curing a mixture comprising a sol-gel component. Figure 2 As shown, curing 208 may include drying the mixture including the sol-gel components disposed on the material substrate 104 and may be performed under ambient conditions, room temperature, and / or at elevated temperatures. The curing temperature is from about 10° C. to about 150° C., such as from about 30° C. to about 100° C., such as from about 50° C. to about 90° C., for example, about 60° C., about 70° C., or about 80° C. Curing 308 may be performed for a period of time, such as from about 1 minute to about 48 hours, such as from about 5 minutes to about 24 hours, such as from about 10 minutes to about 8 hours, such as from about 30 minutes to about 4 hours, for example, about 1 hour.

[0123] After coating 206 and / or curing 208, the sol-gel is suitable for exposure to the external environment and / or application of a second layer 106. Figure 2As shown, placing 210 the organic material of the second layer 106 can be performed before curing 208 is fully completed, for example, placing 210 the second layer 106 can be performed at least partially simultaneously with curing 208. Placing 210 can include painting, spraying, dipping, contacting, adhering, and / or bonding the sol-gel 102 with the organic material to form the second layer 106. The second layer includes a primer, a coating, a fiber-reinforced plastic, or other suitable organic material.

[0124] After coating 210, the sol-gel is suitable for exposure to apply the third layer 112. Placing 212 can include painting, spraying, dipping, contacting, adhering, and / or bonding the second layer 106 with an organic material to form the third layer 112. The third layer includes paint, fiber reinforced plastic, or other suitable organic material.

[0125] Example

[0126] Now refer to Figure 3 , showing potentiodynamic scans of a metal surface coated with a sol-gel pretreatment. Comparative Example 3 is a bare metal surface. Comparative Example 2 is a sol-gel film coated on a metal panel with 3 vol.% of the component. Comparative Example 1 is a sol-gel film coated on a metal panel with >3 vol.% of the component. The inventive example sol-gel is a sol-gel film coated on a metal panel with >3 vol.% of the component plus a corrosion inhibitor.

[0127] As the vol.% of the components in the sol-gel increases, the coating weight / coating thickness increases, thereby increasing the passivation effect of the film on the metal surface. This increase in thickness leads to a decrease in corrosion current.

[0128] The inhibitor has cathodic inhibition properties, resulting in a negative potential shift and a significant reduction in corrosion current.

[0129] Now refer to Figure 4 The corrosion inhibitor in Experiment 1, containing 1,2,4DMcT, provided the strongest corrosion inhibition compared to other organic or chromate inhibitors. A potential-current scan of the inhibitor dissolved in the electrolyte was performed, monitoring the current at -0.8 V with the metal surface acting as the working electrode. The current at -0.8 V indicates that a redox reaction is occurring on the metal surface. Lower ORR values ​​indicate a greater inhibitor effect, e.g., improved inhibitor efficiency.

[0130] Now refer to Figure 5, showing a current-voltage graph of the electrode surface. The current for ORR on the metal surface is -0.8 V. Without wishing to be bound by theory, it is hypothesized that the inhibition of the ORR current is due to inhibitor action, i.e., reaction of the inhibitor with the metal surface. Without wishing to be bound by theory, for thiol inhibitors, it is well known that the inhibitors bind to copper-rich sites on the surface of metal alloys. Inhibitors 1, 2, 3, and 4, which have about 3 wt % to about 15 wt % corrosion inhibitor, exhibited better inhibitor efficiency for corrosion inhibition than the comparative example without corrosion inhibitor.

[0131] Now refer to Figure 6A and 6B The corrosion resistant sol-gel of the present disclosure can be applied to a metal substrate. The corrosion resistant sol-gel layer can be very thin, wherein the thin layer has fewer defects in the sol-gel, such as Figure 6A The corrosion resistant sol-gel layer can be very thick, wherein the adhesion of the sol-gel to the material substrate, primer or topcoat can be improved, e.g. Figure 6B shown.

[0132] like Figure 7 As shown in FIG, the average thickness of the sol-gel of the present disclosure is between 100 nm and 4 μm. Figure 8 As shown, the average coating weight of the present invention is 40 mg / ft 2 Up to 400 mg / ft 2 The increase in sol-gel coating weight improves barrier properties such as absorbance and passivation, e.g. Figure 9 and Figure 10 shown.

[0133] Now refer to Figure 11 , electrical contact resistance increases with increasing coating thickness and weight. Three corrosion-resistant sol-gel sample formulations were prepared, with increasing vol% of the sol-gel components, and more inhibitor was added to the film from Formulation #1 to Formulation #2 and then to Formulation #3. Increasing the vol% of the sol-gel components and inhibitor in the sol-gel resulted in increased coating weight and film thickness. Formulation #1 showed improved corrosion resistance in a salt spray chamber when compared to Formulation #1. However, as film thickness increased, surface contact resistance values ​​also increased.

[0134] Now refer to Figure 12, plots the impedance of the coated panels as a function of the frequency of the applied AC current. The fully chromated stack (chromate conversion coating (CCC) + chromate primer) has the highest impedance, while pretreatments without an inhibitor + chromate primer or with an inhibitor + non-chromate primer have intermediate impedances, and finally pretreatments with CCC + non-chromate primer or with no primer and non-chromate primer have the lowest impedance. Without wishing to be bound by theory, it is possible that the addition of an inhibitor to the pretreatment increases the overall impedance of the film (i.e., improves corrosion resistance), thereby improving the performance of the non-chromate primer. Figures 13A-13F As shown, corrosion is reduced when a material substrate is coated with the corrosion resistant sol-gel of the present disclosure compared to the comparative sol-gel.

[0135] like Figures 14A-14C As shown in FIG. 1 , the corrosion resistance of the chromate-free corrosion-resistant sol-gel of the present disclosure is comparable to that of the sol-gel coated with a chromate corrosion inhibitor. The corrosion resistance of seaside specimens exposed outdoors for 9 months was monitored. Figure 14A The chromate treated stack shown is similar to the Figure 14B and 14C The sol-gel pretreatment shown here with a non-chromate primer stack for corrosion resistance was compared. All samples were found to have good corrosion resistance with no blistering in the field of view and no corrosion on the scribe line, as shown in Figure 2. Figures 14A-14C shown.

[0136] As shown in Table 1, no effect on paint adhesion was observed when the material substrates were coated with the corrosion resistant sol-gel of the present disclosure.

[0137] Table 1. Adhesion properties of sol-gel coated material substrates

[0138]

[0139] Preparation of corrosion-resistant sol-gel

[0140] A "Part A" solution was prepared by adding 22 mL of glacial acetic acid (GAA, Fischer Scientific) to 50 mL of zirconium propoxide (TPOZ, Acros Organics). Care was taken to ensure that all glassware was completely dry to avoid the formation of zirconium hydroxide. The resulting solution was clear and had a pale yellow color. The solution was allowed to stand for 10 minutes, and then 1000 mL of Milli-Q water was added to it. This Part A solution was used for all test matrices.

[0141] 10.8 mL of glycidoxypropyltrimethoxysilane (GTMS, Acros Organics) was then added to 108 mL of Part A in a Thinky™ planetary mixer vessel, mixed thoroughly, and allowed to stand for 30 minutes. 0.6 mL of a 10% volume aqueous solution of Antarox BL-204 (Solvay) was then added, followed by the inhibitor. 2 mm borosilicate glass beads were then added to the Thinky cup to cover the bottom. The solution was then mixed in a Thinky™ planetary mixer (Step 1 - 500 RPM for 30 seconds, Step 2 - 1000 RPM for 30 seconds, Step 3 - 1500 RPM for 1 minute).

[0142] Inhibitor evaluation

[0143] Two inhibitors were obtained from AICLadvanced additives SZP-391JM and 430JM. Both suppressants are jet milled materials with an average particle size of approximately 3 microns and a D99 of approximately 8 microns.

[0144] 1000 and 204 was obtained from WPC technologies. As described in the Results and Discussion section, More than 1000 versions were tested.

[0145] 2,5-Dimercapto-1,34-thiadiazole (DMCT) was obtained from Acros Organics; sodium benzoate and cerium nitrate were from Sigma-Aldrich. These compounds were used as received.

[0146] Panel pre-cleaning

[0147] All 7075-T6 panels were cleaned as follows: degreased in Brulin 815GD for 10 minutes, followed by alkaline cleaning in Bonderite C-AK for 12 minutes and deoxidation in a nitric acid / HF solution for 10 minutes.

[0148] Abrasive blast the 7178-T6 panels with 180-grit brown fused aluminum oxide to remove any residual coating. Then clean the panels as described above for the 7075 panels.

[0149] Conversion coating and pretreatment applications

[0150] The various pretreatments and conversion coatings evaluated included SurTec 650V - SurTec's tri-chrome passivation, Alodine 5900 - Henkel's tri-chrome passivation, Alodine 1200S - Henkel's hexachrome conversion coating, and corrosion inhibitor sol-gels (-1 and -2).

[0151] SurTec coatings are applied using a dipping process. A 5% vol. concentrate solution in water is prepared. The pH of the solution is maintained between 3.7 and 3.95 using 1N H₂SO₄ or 1N NaOH. The cleaned panels are immersed in a SurTec 650V tank for 3 minutes, followed by two to three 15-30 second rinses in tap water, and finally a 15-second rinse in deionized water. The panels are then dried using shop air. The coating is transparent and translucent upon drying.

[0152] Alodine 5900 coating was brush-applied to the panels using the 5900 solution. To apply the coating, clean the panels in a fume hood and brush-apply the solution, keeping the surface wet for three minutes. This was followed by two to three cycles of 15-30 second tap water rinses and 15 second deionized water rinses. The panels were then dried in an oven at 100-120°F for one hour. After drying, the coating had a blue appearance.

[0153] Alodine 1200S was brush-applied to the panels. To apply the brush coating, clean the panels in a fume hood and brush-apply the solution, keeping the surface wet for three minutes. This was followed by several cycles of 15-30 second tap water rinses and 15 second deionized water rinses. The panels were then dried in an oven at 100-120°F for one hour. The coating had a golden color after drying.

[0154] The corrosion-resistant sol-gel of the present disclosure was formulated and applied using a conventional HVLP spray gun and then dried overnight at room temperature.

[0155] Application of primer and topcoat

[0156] All primers and topcoats were applied the day after the panels were pre-treated with the above-mentioned pre-treatment. Both primers and topcoats were applied using conventional HVLP spray guns. Topcoats were applied within 4 hours of primer application, and the coatings were cured at room temperature for 2 weeks. After a two-week drying period, the panels were scribed using a wide knife. Primer and topcoat thicknesses were measured using witness coupons sprayed simultaneously with the panels. Primer and topcoat thicknesses were measured and recorded using a handheld Elcometer thickness gauge.

[0157] Test Matrix

[0158] The test matrix described below evaluated several corrosion-resistant sol-gel formulations using a new accelerated cyclic test method developed according to ASTM B117 and BR&T4. BLIS18-00512 compared corrosion-resistant sol-gel formulations to a control and a trivalent chromium pretreatment alternative. BLIS18-00614 evaluated the standalone corrosion resistance of lower wt% DMCT and Inhibicor 1000 in aqueous solution. BLIS18-00512-2 re-evaluated the sol-gel systems described herein after 3000 hours of exposure to ASTM B117.

[0159] Coating peeling

[0160] Coating and stripping

[0161] The coating was stripped from the test substrate BLIS18-00512-2 using a methylene chloride-based stripper, Bonderite Turco S-ST 5351. To strip the coating, the panels were immersed in the stripper overnight (some for approximately 6 hours). The efficiency of the stripper was recorded.

[0162] Inhibitor Screening in Corrosion Resistant Sol-Gels - Standalone Corrosion Protection

[0163] As shown in Table 2, several inhibitor chemistries were evaluated in the modified sol-gel formulations.

[0164] Table 2. Screening of independent protective inhibitors of 7075-T6 after 24-hour exposure to B117

[0165]

[0166] When 2 wt.% of corrosion inhibitor was added to the sol-gel for testing, The corrosion resistance of SZP-391JM sol-gel is better than 430JM corrosion resistant sol-gel. Addition of 1.24 wt.% corrosion inhibitor loading to the sol-gel resulted in corrosion inhibition after 336 h of exposure to the NSS chamber. Some corrosion products resulting from inhibitor aggregation during drying are visible on the lower portion of the panel. The corrosion resistance of the sol-gel formulation was improved compared to that of the larger particle size sol-gel formulation with a corrosion inhibitor content of 0.53 wt.%, which underwent extensive corrosion after 120 h of exposure in the NSS chamber.

[0167] The corrosion-resistant sol-gel DMCT formulation, soluble in the modified sol-gel, showed improved stand-alone corrosion resistance when tested at a 1.24 wt.% corrosion inhibitor loading in the sol-gel compared to a 2.17 wt.% corrosion inhibitor loading in the sol-gel. No visible corrosion products were observed after 336 hours of stand-alone corrosion testing at 1.24 wt.% DMCT.

[0168] Evaluation of aluminum-rich and lithium-rich primers in corrosion-resistant sol-gel formulations

[0169] Figures 15A-15F The results show that micronized unneutralized PTFE was coated with aluminum (Al)-rich (Av-dec) and lithium (Li)-rich primers (Akzo Nobel Aerodur 2118). Results of the corrosion resistance sol-gel at 1000. After 2000 h of exposure in the NSS chamber, the panel coated with the aluminum-rich primer showed some blistering in the field of view, and white salts were present at the scribe line for both primers.

[0170] When coated with an aluminum-rich primer, the corrosion-resistant sol-gel containing DMCT also exhibited excellent corrosion resistance after 2000 hours of exposure in NSS. The scribe line darkened, but no corrosion products were observed. When coated with a lithium-rich primer, the corrosion-resistant sol-gel containing DMCT exhibited poor corrosion resistance.

[0171] In a new accelerated salt spray corrosion test developed by Chem-Tech, BR&T in Seattle, the The corrosion resistant sol-gel formulations of 1000 and DMCT were further tested.

[0172] 3000h ASTM B117 corrosion testing using corrosion-resistant sol-gel formulations

[0173] 7075-T6 bare panel

[0174] Alodine 1200S

[0175] Regardless of the pretreatment used, all 7075-T6 panels coated with primer RW-7171-64 showed poor corrosion resistance after 3000 h of NSS exposure, with white salt and corrosion on the scribe line and blistering in the field of view. Blistering on panel A-1-1-3 only appeared after 2000 h of exposure.

[0176] like Figures 16A-16DAs shown, the 7075-T6 panels coated with Alodine 1200S performed as well as Aerodur 2118 and PPG CA7231 after 3000 hours of exposure. The panels with Alodine 1200S and the lithium-rich Aerodur 2118 had some blistering in the scribe. The scribes of all the panels coated with Alodine had numerous localized white salt spots in the scribe. After stripping the coating from panel A-1-(1-4)-3, no corrosion was visible on any of the panels in view, including under the small blisters on panel A-1-1-3. The Truco stripper had problems stripping the aluminum-rich primer, as seen from panel A-1-2-1, and the stripper did not remove the Alodine conversion coating from any of the panels. The stripper stripped the lithium-rich primer and both PPG primers.

[0177] Alodine 5900

[0178] like Figures 17A-17D As shown, the triple chrome pretreatment of Henkel Alodine 5900 with Aerodur 2118 lithium-rich primer provides excellent performance. Panel 7075-T6 with Al-rich Av-Dec and PPG CA7231 exhibits blistering at the scribe line. Panel A-2-1-3 is covered with small blisters across almost its entire surface.

[0179] Panel A-2-1-3 shows dark staining of the Al beneath the small blisters in the field of view. All large blisters on the scribe line show signs of pitting beneath the coating. Blisters appeared on panels A-2-1-3 and A-2-4-3 after 1000 hours of NSS exposure.

[0180] Turco stripper was unable to strip the lithium-rich primer from panel A-2-3-(1-2), but was able to strip the PPG and Av-Dec primers.

[0181] SurTec 650V

[0182] Now refer to Figures 18A-18D SurTec 650V demonstrated corrosion resistance and compatibility with Av-Dec, Aerodur 2118, and CA7231 primers. After 3000 hours of exposure, none of these panels showed visible blistering, but small blisters and pitting were observed below the coating on the scribe line in the case of Av-Dec and CA7231 primers. After 2000 hours of NSS exposure, the surface of panel A-3-1-3 was covered with small blisters, but there was no sign of corrosion beneath the blisters.

[0183] All blisters on panel A-3-(1-4)-3 appeared after 2000 h of NSS exposure. Except for Aerodur 2118, all other primers were stripped using Turco stripper.

[0184] Corrosion-resistant sol-gel

[0185] Now refer to Figures 19A-19D The corrosion-resistant sol-gel pretreatment showed improved corrosion resistance when primed with an Al-rich Av-Dec primer. Panels coated with the corrosion-resistant sol-gel, Aerodur 2118, and CA7231 exhibited significant blistering and white salting at the scribe line. Panel A-4-1-3, coated with RW7171-64, exhibited severe blistering in the field of view and at the scribe line.

[0186] After 1000 hours of NSS exposure, blistering was visible on the scribe line of all panels pretreated with Sol-Gel-2. This blistering and corrosion increased with increasing exposure time. Turco stripper performed a poor job of stripping the primer from panels pretreated with Sol-Gel-2. After stripping the primer from panel A-4-(1-4)-3, it was clear that no corrosion beneath the blister was visible, but the blister near the scribe line showed pitting beneath the paint.

[0187] 7178 panel

[0188] Alodine 1200S

[0189] Panels with Alodine 1200S chromate corrosion inhibitor exhibited corrosion performance when primed with RW-7171-64 and Aerodur 2118. Figures 20A-20D As shown, the panels with Alodine 1200S and Av-Dec had some white salt on the score line, while the primer CA7231 had a few blisters along the score line under the primer and a lot of white salt on the score line.

[0190] None of the primers on Panel B-1-(1-4)-1 stripped well using Truco Stripper. There was blistering on the scoreline with pitting underneath the paint.

[0191] Alodine 5900

[0192] Now refer to Figures 21A-21C Panels coated with Aerodur 2118 and RW7171-64 had minimal salt in the scribe line and some creep. Panels coated with the Al-rich Av-Dec primer had salt in the scribe line and some blistering along the scribe line under the primer. When the coating was removed from these panels, pitting was visible along the scribe line below the blistering.

[0193] Truco stripper did not strip panel B-2-1-(1-2) primed with PPG RW-7171-64. The stripper removed the aluminum-rich primer after 1500 hours of exposure, but the primer did not strip after 3000 hours of exposure.

[0194] SurTec 650V

[0195] Now refer to Figures 22A-22C SurTec 650V with an Al-rich Av-Dec primer had minimal salt in the scribe line, and no blistering on the panels. Panels coated with Aerodur 2118 had salt in the scribe line, and RW7171-64 also had salt in the scribe line, along with some blistering. Pitting was clearly visible below the blistering in the scribe line on these panels. RW-7171-64 and the Al-rich Av-Dec primer were not removed with Truco stripper.

[0196] Corrosion Resistant Sol-Gel-2

[0197] Now refer to Figure 23A and 23B The corrosion-resistant sol-gel-coated panel coated with the Al-rich Av-Dec primer exhibited minor blistering. Salt was present along the scribe line, with some blistering along the scribe line. No corrosion was visible beneath the blister, while pitting was observed beneath the primer on panel B-4-2-2, adjacent to the scribe line.

[0198] The corrosion-resistant sol-gel coated panel primed with RW 7171-64 exhibited ~1 / 16" blistering, white salting, and blistering at the scribe line. However, only the blistering at the scribe line showed pitting beneath the primer; no blistering was visible beneath the primer.

[0199] Truco stripper did not strip the primer from these panels pretreated with the corrosion-resistant Sol-Gel-2.

[0200] Ranking of 7075-T6 and 7178Al panels after NSS corrosion testing

[0201] Now refer to Figure 24 and 25 , the coated 7075-T6 and 7178Al panels after corrosion testing were ranked using Methods #1 and #2 described below.

[0202] Method #1 Ranking

[0203] Panels were numerically ranked based on their corrosion performance compared to the corrosion performance of other panels in a group.

[0204] Each panel was rated 1-15 based on scribe appearance, amount of white salt (corrosion product) in the scribe, blistering along the scribe, and blistering away from the scribe, as shown in Table 3. The scribe rating was based on creep measured in inches from the scribe, as shown in Table 4.

[0205] Within groups containing the same pretreatment (and different primers), panels were numerically ranked from 1 to 2, 3, or 4, with 1 being the best candidate and 4 being the worst. 7075-T6 Al panels were evaluated after 1000, 2000, and 3000 hours of exposure, and 7178 Al panels were evaluated after 1500 and 3000 hours of exposure.

[0206] SurTec 650V panels coated with Aerodur 2118, AvDec PT27703, AvDec-GK15-002E1, and PPG CA7231 exhibited corrosion resistance up to 9 months after application. The corrosion resistant sol-gel of the present disclosure coated with AvDec GK15-002E1 exhibited corrosion resistance up to 9 months after application.

[0207] Table 3. Corrosion level determination for Method #1

[0208]

[0209] Table 4. Determination of the marking grade for Method 1

[0210] Marking level describe A No peristalsis B 0 to 1 / 64” C 1 / 64” to 1 / 32” D 1 / 32” to 1 / 16” E 1 / 16” to 1 / 8” F 1 / 8” to 3 / 16” G 3 / 16” to 1 / 4” H 1 / 4” to 3 / 8”

[0211] Method #2 Ranking

[0212] Each panel was assigned an independent score regardless of the performance of the other panels in the test matrix. The score / ranking for Method #2 was determined using 3 factors: 1) General Corrosion (GC) rating; 2) Blister Size (BS) rating; and 3) Blister Frequency (BF) rating. Each 7075-T6 panel that completed 1000h, 2000h, and 3000h exposure was assigned a numerical value for each of the 3 criteria, and the total score was calculated using the following equation (1).

[0213] The scores determined for each interval are weighted according to Equation 1 below, so that scores with longer exposure times receive greater weight. The 1000-hour score is multiplied by 0.2, the 2000-hour score is multiplied by 0.3, and the 3000-hour score is multiplied by 0.5. These weighted scores are then added together, and the sum is divided by 2 to determine the final Method #2 score for each panel.

[0214] Method #2 Total Score = ((((BS Score) 1000h *BF score 1000h )+GC score 1000h )*0.2)+(((BS score 2000h *BF score 2000h )*0.3)+(((BS score 2000oh *BF score 3000h )+GC score 3000h)*0.5))*0.5

[0215] Equation (1)

[0216] The general corrosion grade is determined based on the pitting observed around the scribe line and in the field of view on the debonded panel. The panel with the least corrosion is assigned the highest value of 10, while the panel with the most corrosion is assigned the lowest value of 2.

[0217] For blister size and frequency, a score was assigned based on the size and density of blisters observed in the field of view and on the scribe line of the coated panel. Panels with no blisters were assigned a blister frequency score of 1.

[0218] The composite score weighting scheme for the 7178-T6 panel was modified because there are only two intervals (at 1500 h and 3000 h) instead of three intervals (1000 h, 2000 h, and 3000 h) in the 7075-T6.

[0219] For the 7178-T6 panel, the score after 1500 hours of exposure is multiplied by 0.33, and the score after 3000 hours of exposure is multiplied by 0.67. As before, these two scores are added together and the total is divided by 2 to obtain the final score.

[0220] The criteria for determining blister size and blister frequency for 7178 panels are the same as for 7075-T6 panels.

[0221] Comparison of corrosion resistance of coated 7075-T6 and 7178Al panels after NSS and cyclic accelerated corrosion tests

[0222] Method #2 scoring allows comparison of the corrosion performance of similar coating stacks between two different accelerated corrosion tests.

[0223] Now refer to Figure 26 and 27 , a significant difference in the performance of the stacks containing the corrosion-resistant Sol-Gel-2 coating was observed. The corrosion-resistant Sol-Gel-2 / Al-rich Av-Dec coating was corrosion-resistant under cyclic accelerated corrosion test conditions, but not in the ASTM B117 test.

[0224] Similar effects were observed with magnesium (Mg)-rich primers after ASTM B117 testing. The Mg-rich primers were observed to exhibit corrosion resistance under outdoor exposure and actual test conditions, but not in accelerated corrosion testing (according to ASTM B117 conditions). A passive MgCO3 layer was formed upon outdoor exposure, providing both anodic and cathodic corrosion protection. However, upon exposure to ASTM B117 conditions, a thin, porous Mg(OH)2 layer formed, which exhibited lower corrosion resistance.

[0225] Other aspects

[0226] The present disclosure provides the following embodiments, etc., wherein each embodiment may be considered to optionally include any optional aspects thereof and combinations thereof.

[0227] Clause 1. A coated substrate comprising:

[0228] Metal substrate; and

[0229] A sol-gel coating disposed on a metal substrate, the sol-gel coating comprising a sol-gel comprising:

[0230] about 3 wt % to about 15 wt % of an organic corrosion inhibitor,

[0231] surfactants, and

[0232] The reaction product of an epoxy-containing organosilane, a metal alkoxide and an acid.

[0233] Item 2. The coated substrate of Item 1, further comprising an organic primer coating comprising an organic primer disposed on the sol-gel coating.

[0234] Clause 3. The coated substrate according to Clause 1 or 2, wherein the organic primer coating further comprises a plurality of metal particles.

[0235] Clause 4. The coated substrate according to any one of clauses 1 to 3, wherein the metal is a combination of:

[0236] Aluminum, a salt of aluminum or a cation of aluminum, and

[0237] Magnesium, a salt of magnesium, or a cation of magnesium.

[0238] Item 5. The coated substrate according to any one of Items 1 to 4, wherein the organic primer is a polysiloxane or an epoxy resin.

[0239] Item 6. The coated substrate of any one of Items 1 to 5, wherein the epoxy resin is an amine-cured epoxy resin.

[0240] Item 7. The coated substrate according to any one of Items 1 to 6, wherein the surfactant is ethylene oxide alcohol, propylene oxide alcohol, or ethylene oxide propylene oxide alcohol.

[0241] Clause 8. The coated substrate of any one of Clauses 1 to 7, further comprising an organic topcoat disposed over the primer coating.

[0242] Clause 9. The coated substrate of any one of clauses 1 to 8, wherein the organic topcoat is a polyurethane.

[0243] Clause 10. The coated substrate of any one of Clauses 1 to 9, wherein the thickness of the organic topcoat is from about 2 mils to about 3 mils, and the thickness of the organic primer is from about 0.3 mils to about 2.5 mils.

[0244] Item 11. The coated substrate of any one of Items 1 to 10, wherein the organic corrosion inhibitor has two or more thiol moieties.

[0245] Item 12. The coated substrate of any one of Items 1 to 11, wherein the organic corrosion inhibitor is a mercaptothiadiazole.

[0246] Item 13. The coated substrate according to any one of Items 1 to 12, wherein the dimercaptothiadiazole is 2,5-dimercapto-1,3,4-thiadiazole.

[0247] Clause 14. The coated substrate according to any one of clauses 1 to 13, wherein the metal substrate is an aluminum substrate.

[0248] Clause 15. The coated substrate of any one of Clauses 1 to 14, wherein the aluminum substrate is a 7075-T6 aluminum substrate or a 7178 aluminum substrate.

[0249] Item 16. The coated substrate of any one of Items 1 to 15, wherein the sol-gel coating has a thickness of about 50 nm to about 4 microns.

[0250] Item 17. The coated substrate of any one of Items 1 to 16, wherein the sol-gel coating has a thickness of about 100 nm to about 2.5 microns.

[0251] Clause 18. The coated substrate of any one of clauses 1 to 17, wherein the weight of the sol-gel coating is about 30 mg / ft 2 About 400mg / ft 2 .

[0252] Clause 19. The coated substrate of any one of clauses 1 to 18, wherein the weight of the sol-gel coating is about 250 mg / ft 2 About 1000mg / ft 2 , such as about 250mg / ft 2 About 350mg / ft 2 .

[0253] Item 20. The coated substrate of any one of Items 1 to 19, wherein the sol-gel coating has an organic corrosion inhibitor concentration of about 5 wt% to about 10 wt%.

[0254] Item 21. The coated substrate of any one of Items 1 to 20, wherein the sol-gel coating has an organic corrosion inhibitor concentration of about 10 wt% to about 15 wt%.

[0255] Item 22. The coated substrate of any one of Items 1 to 21, wherein the sol-gel coating has an organic corrosion inhibitor concentration of about 12 wt% to about 15 wt%.

[0256] Item 23. The coated substrate of any one of Items 1 to 22, wherein the organic corrosion inhibitor is not an organometallic corrosion inhibitor.

[0257] Item 24. The coated substrate of any one of Items 1 to 23, wherein the organosilane is glycidoxypropyltrimethoxysilane, the acid is acetic acid, and the metal alkoxide is zirconium propoxide.

[0258] Clause 25. A method of preparing a coated substrate, the method comprising:

[0259] The sol-gel coating is applied to a metal substrate to form a sol-gel coating comprising about 3 wt % to about 15 wt % of a corrosion inhibitor.

[0260] Clause 26. The method according to Clause 25, further comprising:

[0261] A primer coating is applied to the sol-gel coating to form a primer coating, the primer coating including a metal.

[0262] Clause 27. The method of clause 25 or 26, wherein applying the sol-gel coating comprises mixing the corrosion inhibitor with an organosilane and a metal alkoxide, wherein the volume ratio of the organosilane to the metal alkoxide is from about 5% to about 20%, wherein the metal alkoxide has been pretreated with an acid.

[0263] Item 28. The method of any one of Items 25 to 27, wherein the volume ratio of the organosilane to the metal alkoxide is from about 9% to about 11%.

[0264] Clause 29. The method of any one of Clauses 25 to 28, wherein the mixed corrosion inhibitor has a D90 particle size of about 2 microns to about 5 microns.

[0265] Clause 30. The method of any one of Clauses 25 to 29, further comprising pre-treating the metal substrate before applying the sol-gel coating to the metal substrate.

[0266] Clause 31. The method of any one of Clauses 25 to 30, wherein the pretreatment comprises immersing the metal substrate in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH.

[0267] Clause 32. The method of any one of Clauses 25 to 31, wherein the solution comprises, per liter of solution, from about 3 grams to about 22 grams of a water-soluble trivalent chromium salt, from about 1.5 grams to about 11.5 grams of an alkali metal hexafluorozirconate, from about 0 grams to about 10 grams of a water-soluble thickener, and from about 0 grams to about 10 grams of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and combinations thereof.

[0268] Clause 33. A coated substrate comprising:

[0269] a metal substrate; and a sol-gel coating disposed on the metal substrate, the sol-gel coating comprising a sol-gel comprising: from about 3 wt % to about 15 wt % of an organic corrosion inhibitor, a surfactant, and a reaction product of an epoxy-containing organosilane, a metal alkoxide, and an acid, based on the volume of the sol-gel coating.

[0270] Clause 34. The coated substrate of Clause 33, further comprising an organic primer coating, the coating comprising an organic primer disposed on the sol-gel coating.

[0271] Clause 35. The coated substrate of Clause 34, wherein the organic primer coating further comprises a plurality of metal particles.

[0272] Item 36. The coated substrate according to Item 33 or 34, wherein the organic primer is a polysiloxane or an epoxy resin, wherein the epoxy resin is optionally an amine-cured epoxy resin.

[0273] Item 37. The coated substrate according to any one of Items 33 to 36, wherein the surfactant is ethylene oxide alcohol, propylene oxide alcohol, or ethylene oxide propylene oxide alcohol.

[0274] Clause 38. The coated substrate of any one of Clauses 33 to 37, further comprising an organic topcoat disposed over the primer coating.

[0275] Item 39. The coated substrate of any one of Items 33 to 38, wherein the organic corrosion inhibitor has two or more thiol moieties.

[0276] Item 40. The coated substrate of Item 39, wherein the organic corrosion inhibitor is a mercaptothiadiazole, wherein the dimercaptothiadiazine is optionally 2,5-dimercapto-1,3,4-thiadiazole.

[0277] Item 41. The coated substrate of any one of Items 33 to 40, wherein the sol-gel coating has an organic corrosion inhibitor concentration of about 5 wt% to about 15 wt% by volume of the sol-gel coating.

[0278] Item 42. The coated substrate of any one of Items 33 to 41, wherein the organosilane is glycidoxypropyltrimethoxysilane, the acid is acetic acid, and the metal alkoxide is zirconium propoxide.

[0279] Clause 43. A method of preparing a coated substrate, the method comprising:

[0280] The sol-gel coating is applied to a metal substrate to form a sol-gel coating, the sol-gel coating including a corrosion inhibitor in an amount of about 3 wt % to about 15 wt % based on the volume of the sol-gel coating.

[0281] Clause 44. The method according to clause 43, further comprising:

[0282] A primer coating is applied to the sol-gel coating to form a primer coating, the primer coating comprising a metal, wherein applying the sol-gel coating optionally comprises mixing a corrosion inhibitor with an organosilane and a metal alkoxide, wherein the volume ratio of the organosilane to the metal alkoxide is from about 5% to about 20%, wherein the metal alkoxide has been pretreated with an acid.

[0283] Item 45. The method of Item 44, wherein the volume ratio of the organosilane to the metal alkoxide is from about 9% to about 11%, and / or wherein the corrosion inhibitor after mixing has a D90 particle size from about 2 microns to about 5 microns.

[0284] Item 46. The method of any one of Items 43 to 45, further comprising pretreating the metal substrate before applying the sol-gel coating to the metal substrate, wherein the pretreatment optionally comprises immersing the metal substrate in a solution maintained at a pH between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH.

[0285] Clause 47. The method of clause 46, wherein the solution comprises, per liter of solution, from about 3 grams to about 22 grams of a water-soluble trivalent chromium salt, from about 1.5 grams to about 11.5 grams of an alkali metal hexafluorozirconate, from about 0 grams to about 10 grams of a water-soluble thickener, and from about 0 grams to about 10 grams of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, a cationic surfactant, and combinations thereof.

[0286] Overall, the sol-gels of the present disclosure provide standalone corrosion resistance and the performance of non-chromate primers. The sol-gels of the present disclosure maintain adequate paint adhesion through the use of corrosion inhibitors and provide cathodic corrosion protection. The sol-gels of the present disclosure allow for an easily applied spray sol-gel that provides corrosion resistance, avoids the use of chromate primers, and is free of heavy metals.

[0287] Although we have described preferred aspects, those skilled in the art will readily recognize that substitutions, variations, and modifications may be made without departing from the spirit of the present invention. Therefore, the claims are to be interpreted literally, with support from the full range of equivalents known to those skilled in the art, based on this specification. These examples illustrate the present disclosure but are not intended to limit it. Therefore, the present disclosure and the claims are to be defined and limited only as necessary in light of the relevant prior art.

Claims

1. A coated substrate comprising: Metal substrate; and A sol-gel coating disposed on the metal substrate, the sol-gel coating comprising a sol-gel, the sol-gel comprising: Based on the volume of the sol-gel coating, about 3 wt % to about 15 wt % of an organic corrosion inhibitor, a surfactant, and The reaction products of epoxy-containing organosilanes, metal alkoxides and acids.

2. The coated substrate of claim 1, further comprising an organic primer coating comprising an organic primer disposed on the sol-gel coating.

3. The coated substrate of claim 2, wherein the organic primer coating further comprises a plurality of metallic particles.

4. A coated substrate according to claim 2 or 3, wherein the organic primer is a polysiloxane or an epoxy resin, wherein the epoxy resin is optionally an amine-cured epoxy resin.

5. A coated substrate according to any one of claims 1 to 4, wherein the surfactant is ethylene oxide alcohol, propylene oxide alcohol or ethylene oxide propylene oxide alcohol.

6. The coated substrate according to any one of claims 1 to 5, further comprising an organic topcoat disposed on the primer coating.

7. The coated substrate according to any one of claims 1 to 6, wherein the organic corrosion inhibitor has two or more thiol moieties.

8. The coated substrate of claim 7, wherein the organic corrosion inhibitor is a mercaptothiadiazole, wherein the dimercaptothiadiazole is optionally 2,5-dimercapto-1,3,4-thiadiazole.

9. The coated substrate of any one of claims 1 to 8, wherein the sol-gel coating has the organic corrosion inhibitor at a concentration of about 5 wt% to about 15 wt% by volume of the sol-gel coating.

10. The coated substrate of any one of claims 1 to 9, wherein the organosilane is glycidoxypropyltrimethoxysilane, the acid is acetic acid, and the metal alkoxide is zirconium propoxide.

11. A method for preparing a coated substrate, the method comprising: A sol-gel coating is applied to a metal substrate to form the sol-gel coating, the sol-gel coating comprising a corrosion inhibitor in an amount of about 3 wt % to about 15 wt % based on the volume of the sol-gel coating.

12. The method according to claim 11, further comprising: A primer coating is applied onto the sol-gel coating to form the primer coating, the primer coating comprising a metal, wherein applying the sol-gel coating optionally comprises mixing the corrosion inhibitor with an organosilane and a metal alkoxide, wherein the volume ratio of the organosilane to the metal alkoxide is from about 5% to about 20%, wherein the metal alkoxide has been pretreated with an acid.

13. The method of claim 12, wherein the volume ratio of the organosilane to the metal alkoxide is about 9% to 11% and / or wherein the corrosion inhibitor after mixing has a D90 particle size of about 2 microns to about 5 microns.

14. The method according to any one of claims 11 to 13, further comprising pre-treating the metal substrate before applying the sol-gel coating to the metal substrate, wherein the pre-treatment optionally comprises immersing the metal substrate in a solution maintained at a pH value between 3.7 and 3.95 using 1N H2SO4 or 1N NaOH.

15. The method of claim 14, wherein the solution comprises from about 3 grams to about 22 grams of a water-soluble trivalent chromium salt, from about 1.5 grams to about 11.5 grams of an alkali metal hexafluorozirconate, from about 0 grams to about 10 grams of a water-soluble thickener, and from about 0 grams to about 10 grams of a water-soluble surfactant selected from the group consisting of a nonionic surfactant, an anionic surfactant, and a cationic surfactant, and combinations thereof, per liter of solution.